Utopian Variations: Utopia in Literature, Film, and Popular Culture - Seeger, Sean (Ralahine Utopian Studies, 2025)
Utopian Variations is a comparative critical study of a variety of kinds of utopia and utopian discourse. Rather than focusing on more familiar forms of utopia, the book considers utopia in relation to a range of topics that have received less attention within utopian studies, including literary modernism, postsecularism, transhumanism, antihumanism, xenofeminism, the Covid-19 pandemic, recent speculation about postcapitalism, and utopianism since the 2007–8 financial crisis. The book also makes an entirely original argument for a re-evaluation of the concept of the utopian blueprint that breaks with academic orthodoxy in this area. As well as drawing on literature, film, and popular culture, there is extensive engagement with social theory, cultural theory, and queer theory, resulting in a rich, wide-ranging study.A small book on very big ideas. The title tells us there’ll be variety, and Sean Seeger delivers that variety not just in terms of the forms discussed but of the texts explored too. Utopian Variations is both accessible and interesting. The writing is clear and to the point but there’s no sacrificing on the detail. Seeger focuses his attention on the forms of utopia and utopianism that have received less attention in academic work to date, and his chronological approach makes it easy to track the evolution of the central ideas explored. I learnt a lot reading this book and have been introduced to a great many new texts.– Matthew Leggatt, University of Winchester